The ERA5 global reanalysis: Preliminary extension to 1950. (9th November 2021) - Bell, Bill; Hersbach, Hans; Simmons, Adrian; Berrisford, Paul; Dahlgren, Per; Horányi, András; Muñoz‐Sabater, Joaquín; Nicolas, Julien; Radu, Raluca; Schepers, Dinand; Soci, Cornel; Villaume, Sebastien; et al.
Abstract: The extension of the ERA5 reanalysis back to 1950 supplements the previously published segment covering 1979 to the present. It features the assimilation of additional conventional observations, as well as improved use of early satellite data. The number of observations assimilated increases from 53, 000 per day in early 1950 to 570, 000 per day by the end of 1978. Accordingly, the quality of the reanalysis improves throughout the period, generally joining seamlessly with the segment covering 1979 to the present. The fidelity of the extension is illustrated by the accurate depiction of the North Sea storm of 1953, and the events leading to the first discovery of sudden stratospheric warmings in 1952. Time series of ERA5 global surface temperature anomalies show temperatures to be relatively stable from 1950 until the late 1970s, in agreement with the other contemporary full‐input reanalysis covering this period and with independent data sets, although there are significant differences in the accuracy of representing specific regions, Europe being well represented in the early period but Australia less so. The variability of ERA5 precipitation from month to month agrees well with observations for all continents, with correlations above 90% for most of Europe and generally in excess of 70% for North America, Asia and Australia. The evolution of upper air temperatures, humidities and winds shows smoothly varying behaviour, including tropospheric warming and stratospheric cooling, modulated by volcanic eruptions. The Quasi‐Biennial Oscillation is well represented throughout. Aspects to be improved upon in future reanalyses include the assimilation of tropical cyclone data, the spin‐up of soil moisture and stratospheric humidity, and the representation of surface temperatures over Australia. Abstract : This article describes the preliminary extension of the ERA5, ECMWF's fifth‐generation global atmospheric reanalysis, to 1950. ERA5 provides coherent hourly estimates of the global atmosphere, land surface and ocean waves at a horizontal resolution of 31 km over the last 70 years, a significant advance with respect to its predecessor ERA‐Interim. The figure shows ERA5 monthly anomalies in global temperature, ozone and humidity for 1950–2020 with respect to the ERA5 monthly mean climate over the period 1981–2010.